2011
DOI: 10.1002/chem.201101862
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Synthesis of Massadine: A Unified Strategy for the Stereoselective Synthesis of the Carbocyclic C,D‐Ring Subunit

Abstract: Massadine is a hexacyclic marine natural product, which belongs to the family of pyrrole-imidazole alkaloids. Herein, we describe a unified approach to the C,D-ring subunit of this sponge metabolite based on the exploitation of a norbornene scaffold for the stereocontrolled construction of massadine's carbon skeleton. Highlights of the sequence presented include the application of a stereospecific norbornyl rearrangement for facile introduction of an oxygen at the C7-position within the norbornene nucleus, a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…More recently, Carreira's group published a series of three contributions relating to the enantioselective synthesis of fragments of massadine, in which regioselective ozonolytic end‐group differentiation cleavage of a norbornene skeleton was used as the key reaction 7,19,20. In their first example, they reported that ozonolytic cleavage of the norbornene 84a (Scheme ) distinguished between the two sp 2 ‐hybridized carbons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Carreira's group published a series of three contributions relating to the enantioselective synthesis of fragments of massadine, in which regioselective ozonolytic end‐group differentiation cleavage of a norbornene skeleton was used as the key reaction 7,19,20. In their first example, they reported that ozonolytic cleavage of the norbornene 84a (Scheme ) distinguished between the two sp 2 ‐hybridized carbons.…”
Section: Discussionmentioning
confidence: 99%
“…They subjected the acetal 89a (Scheme ) to the ozonolytic cleavage conditions to isolate the ester/aldehyde 90a as the only isomer, in yields ranging from 44 to 54 % 20. This transformation suffered from undesired side reactions, predominantly during the second stage of the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…165 Compound 130 displayed signicant growth inhibitory activity against the Gram-positive bacteria S. aureus and B. subtilis; Gram-negative bacteria E. coli and Pseudomonas aeruginosa; and the fungus C. albicans. [169][170][171][172] Wright and co-workers screened the extracts of 65 sponges, gorgonians, hard corals and sponge-associated bacteria from depths of 50 and 1000 m, giving rise to a 42% bioactivity hit rate overall, and an impressive 72% for sponge and gorgonian extracts. [169][170][171][172] Wright and co-workers screened the extracts of 65 sponges, gorgonians, hard corals and sponge-associated bacteria from depths of 50 and 1000 m, giving rise to a 42% bioactivity hit rate overall, and an impressive 72% for sponge and gorgonian extracts.…”
Section: Order Halichondridamentioning
confidence: 99%
“…The structurally unique compound exhibited potent antimitotic activity (IC 50 < 10 nM) against human A549 lung adenocarcinoma, PANC-1 pancreatic carcinoma, DLD-1 colorectal carcinoma, and murine P388 leukemia cell lines. 187 The marine sponge T. swinhoei, obtained from Uchelbeluu Reef in Palau at a depth of 100 m, was reported to produce three new anabaenopeptin-like peptides, paltolides A-C (168)(169)(170). 185,186 The deep-sea sponges Theonella swinhoei and Theonella cupola, obtained at a depth of 100-120 m and 90 m, respectively, yielded the new sulfated cyclic depsipeptide, mutremdamide A (161), and six new highly N-methylated peptides, koshikamides C-H (162)(163)(164)(165)(166)(167).…”
Section: Order Lithistidamentioning
confidence: 99%
“…125,126 They also successfully constructed a fully functionalized massadine synthetic intermediate in 2011. 127,128 Specifically, they prepared ketone 24 from allyldimethylsilyl cyclopentadiene and dimethyl fumarate by a Diels–Alder reaction followed by Tamao oxidation (Fig. 6).…”
Section: The Higher Order Pyrrole-imidazole Alkaloidsmentioning
confidence: 99%